Space and Salvation in Colette's Chéri and La Fin de Chéri - Ann Leone Philbrick (Studies in 20th & 21st Century Literature, 1984)
Colette's critics often seem to dismiss all but her autobiographical creatures as whimsical and inarticulate. Her characters are frequently less eloquent than the spaces they create and inhabit; this observation offers an approach to Chéri and La Fin de Chéri that invites us to read them as two of Colette's most ambitious and authentic works. Here are stories of compromises with the containers of one's life and identity: streets, salons, boudoirs, and, ultimately, the body. Indeed, the self and its containers function symbiotically. Chéri makes no effort to direct this relationship, and kills himself when the world finally seems inscrutable and formless; his older mistress, Léa, responds joyfully—or with melancholic respect—to the surfaces and limits of her world. We are left with a harsher insight into Colette's vision than we are accustomed to. She suggests that survival lies not in the endless definition of one's place in the world, but in its recognition and a loving, even fearing, homage.